Faktor-Faktor yang Mempengaruhi Kepuasan Pelanggan di Kedai Kopitiam Laoban Surabaya - Falencia Sally Marcella Dermawan; Iva Khoiril Mala (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The development rapidly growing of the Indonesian food and beverage industry increases the risk of business competition. To develop and overcome the food and beverage industry, Laoban Surabaya must have the advantage of being a kopitiam shop. The aim of this research is to cover all components that can influence customer satisfaction. Qualitative research uses interviews to collect data. The data analysis method used was data reduction and drawing conclusions, with eight respondents being owners and visitors to Laoban Surabaya. The research results show that product quality, price and service are three components that influence customer satisfaction. In terms of product quality, providing high quality food and drinks with unique flavors that can be enjoyed by everyone. In terms of price, affordable price offers start from IDR 10,000 to IDR 50,000. In terms of service quality, ensuring customer comfort, friendly and alert service, and fast service.